The mechanics of breathing during swimming - Leahy, M. G.; Summers, M. N.; Peters, C. M.; Molgat-Seon, Y.; Geary, C. M.; Sheel, A.W. (Medicine & Science in Sports & Exercise, 2019)
The thorax undergoes unique conditions while swimming. Hydrostatic pressure from water immersion places an external load on the thorax and increases airway resistance, and the horizontal body position results in central venous engorgement and an associated reduction in lung compliance. The aforementioned factors likely increase the work of breathing (Wb); however, this hypothesis remains untested.